Pengembangan Produk Ikan Cakalang (Katsuwonus pelamis) Asap Metode Asap Cair Kulit Buah Nipah (Nypa fruticans) serta Evaluasi Bakteri Patogennya - Mardiyana, Mardiyana; Handayani, Murni; Fadlilah, Ilma; Aza Fauziana, Noer (JURNAL AGROINDUSTRI HALAL, 2026)
Skipjack tuna (Katsuwonus pelamis) is a leading fish commodity often processed into smoked products. The use of liquid smoke as a modern smoking alternative is growing, yet liquid smoke from nipah fruit skin (Nypa fruticans) remains underutilized. This study aims to determine the optimal concentration of nipah based liquid smoke for skipjack tuna smoking based on sensory characteristics and protein content also evaluation of bacteria pathogen. An experimental method was applied using a completely randomized design with four concentrations (5%, 10%, 15%, and 20%), evaluated for appearance, aroma, taste, texture, protein level using kjehdahl method, and bacteria pathogenic using SSA and EMBA test. Sensory tests revealed that the 20% treatment scored highest in aroma, taste, and texture, while the highest protein content was found at 15% and 20%. The results of the pathogenic bacteria evaluation showed no detection of Salmonella and Escherichia coli bacteria. Statistical analysis showed no significant differences among treatments (P>0.05), but the De Garmo method indicated that the 20% concentration had the highest effectiveness score (NH=1.19). In conclusion, the 20% liquid smoke concentration is the best treatment for smoking skipjack tuna using nipah fruit skin liquid smoke.